Syntheses of five new layered quaternary chalcogenides SrScCuSe3, SrScCuTe3, BaScCuSe3, BaScCuTe3, and BaScAgTe3: crystal structures, thermoelectric properties, and electronic structures. Issue 17 (2nd August 2021) - Ishtiyak, Mohd; Jana, Subhendu; Karthikeyan, R.; Ramesh, M.; Tripathy, Bikash; Malladi, Sairam K.; Niranjan, Manish K.; Prakash, Jai
Abstract : Five new layered transition metal-based chalcogenides (SrScCuSe3, SrScCuTe3, BaScCuSe3, BaScCuTe3, and BaScAgTe3 ) were discovered by the exploratory solid-state method. Abstract : Copper/silver-containing chalcogenides have recently attracted significant interest for their promising thermoelectric applications. In this article, we report the syntheses of five new layered quaternary Cu/Ag-containing chalcogenides: SrScCuSe3, SrScCuTe3, BaScCuSe3, BaScCuTe3, and BaScAgTe3 . The single-crystal X-ray diffraction studies show that all the Cu-containing compounds are isostructural and crystallize in the orthorhombic crystal system in the Cmcm space group. Interestingly, the crystal structure of isoelectronic BaScAgTe3 does not adopt the same structure type as observed for AkScCuQ3 (Ak = Sr/Ba; Q = Se/Te). Instead, it crystallizes in the primitive orthorhombic Pnma space group. The crystal structures of all these compounds are two-dimensional consisting of 2∞[ScMQ3 ] 2− layers (M = Cu/Ag) separated by Ak 2+ cations. The building blocks of these structures are distorted tetrahedral MQ4 and octahedral ScQ6 units. The arrangement and sharing of the MQ4 and ScQ6 units are slightly different for the two structure types, AkScCuQ3 (Ak = Sr and Ba; Q = Se and Te) and BaScAgTe3 . Resistivity study confirms the metallic behavior for BaScCuTe3 . The positive sign of thermopower values suggests holes as the charge carriers. The value of the thermoelectric figure of merit ( zT ) for polycrystalline BaScCuTe3 was found to be enhanced on increasing the temperature with a maximum zT value of 0.34 at 779 K. In addition, we have also studied the structural and electronic properties of BaScCuTe3 and BaScAgTe3 within the framework of density functional theory (DFT).